An X Band Radio Channel Model for Propagation Through the Solar Corona. Issue 9 (3rd September 2018) - Stocker, A. J.; Siddle, D. R.; Warrington, E. M.; Mariotti, G.; Silvestri, D.; Zeqaj, A.; Tortora, P.; Argyriou, A.; De Vicente, J.; Abello, R.; Mercolino, M.
Abstract: Spacecraft communication systems operating at X band are strongly affected when the propagation path passes close to the Sun (which can be characterized by the Sun‐Earth‐Probe, SEP, angle). In this paper, a channel model that can generate a time series of signal amplitude and phase, and hence the signal in‐phase and quadrature values, is presented. For X band, the channel model reproduces the observations well for SEP > 0.8°. While the model has not been experimentally validated at SEP angles below 0.8°, the behavior is consistent with measurements reported in the literature and is therefore likely to be suitable for use, with caution, in that region too. Plain Language Summary: When spacecraft are on the other side of the Sun as seen from the Earth, the solar corona (i.e., the Sun's atmosphere ) can hinder radio communication between the ground station and the spacecraft. In this paper, we present a new model that helps characterize effects of the solar corona on radio signals and that can then be used to test how well current, or future, communication technologies will cope with such conditions. Key Points: A channel model has been developed to simulate the effects of the solar corona on X band communication signals The model successfully reproduces the behavior of experimental observations The model can be used in complete system simulators